Oral Administration of Tualang and Manuka Honeys Modulates Breast Cancer Progression in Sprague-Dawley Rats Model - Ahmed, Sarfraz; Sulaiman, Siti Amrah; Othman, Nor Hayati (Hindawi Publishing Corporation, 2017)
Breast cancer has been recognized as the leading cause of death in women worldwide. Research has shown the importance of complementary and alternative therapies in cancer. In this study, we investigated the antitumoural therapeutic effects ofMalaysian Tualang honey (TH) and Australian/New Zealand Manuka honey (MH) against breast cancer in rats. Thirty syngeneic virgin female Sprague-Dawley (SD) rats were induced by the carcinogen 1-methyl-1-nitrosourea (MNU) 80mg/kg. The treatment started when first palpable tumour reached 10–12mm in size by dividing rats into following groups: Group 0 (negative control); Group 1 (positive control); and Groups 2 and 3 which received 1.0 g/kg body weight/day of TH and MH, respectively, for 120 days. The data demonstrate that cancer masses in TH and MH treated groups showed a lower median tumour size, weight, and multiplicity compared with the nontreated positive control (